An assessment of the bean stem maggot (Ophiomya spp.) damage at Greytown during the 1995 season - Jarvie, JA; Ampofo, James Kwasi O. (International Center for Tropical Agriculture, 1995)
Bean Stem Maggot (BSM) is a serious production problem in many African countries. In South Africa, the problem receives very little research and extension attention. This study set out to assess the magnitude of the BSM problem at Greytown during the 1995 season. Using a split-plot trial, split for insecticide or no insecticide, cultivar reaction to BSM was determined. The trial contained sixteen cultivar entries, including three local controls. Assessment of the potential threat of BSM to local production was made by comparisons across treatments using the local control variety Wartburg. Seed treatment with endosulfan was effective in eliminating seedling mortality due to BSM. In comparing the treated versus untreated plots of Wartburg, the plant population reduction attributable to BSM was 10.9 percent. On average; treated Wartburg plots supported 0.93 BSM larvae/pupae plant(-1) compared to 3.7 BSM larvae/pupae plant(-1) in the untreated plots. The resultant yield loss due to the combined effect of plant stand reduction and the deleterious effects of the larvae and pupae amounted to 11.39 percent. With subsistence agriculture in KwaZulu Natal (KZN), where low fertility and late plantings are the norm, the effects of BSM can be expected to be more severe still. The findings of this study justify the call for more extension and research resources to be allocated to the BSM problem.